Cross-reactivity with Brazilian strains of Neisseria meningitidis B after immunization with outer membrane vesicles - Trzewikoswki de Lima, Gabriela (Ther Adv Vaccines Immunother, 2019)
BACKGROUND: Immunization against Neisseria meningitidis is important for public health. Vaccines composed of cross-reactivity antigens avoid strain-specific responses, ensuring more comprehensive protection. METHODS: The cross-reactivity between three strains from the last outbreak of N. meningitidis in Brazil was assessed in our studies, using enzyme-linked immunosorbent assay (ELISA) and immunoblotting assays. RESULTS: Both assays verifed a similar humoral response between the strains evaluated. Patterns of antigen recognition differed with each dose evaluated. CONCLUSIONS: We observed that immunization with N. meningitidis B outer membrane vesicles (OMVs) led to the production of antibodies that recognized antigens of heterologous strains, indicating possible protection against these evaluated strains.